PELATIHAN DESAIN GRAFIS BAGI SISWA- SISWI SMA NEGERI 12 BANDAR LAMPUNG GUNA MELAHIRKAN GENERASI Z YANG KOMPETITIF - Ade Moussadecq; Putri Handayani; Helen Larrisa (Jurnal Publika Pengabdian Masyarakat, 2024)
The current era of digital technology requires an increase in competencies that must be possessed by the next generation, especially in the world of work. One of the recommended competencies for the next generation is the competency in the field of graphic design. Generation Z has created a way to interact significantly due to the influence of digital media. One aspect that affects their interaction is a graphic design, especially modern graphic design. The development of social media is very central in shaping the perception of this generation of interest in graphic design. The 12th Senior High School of Bandar Lampung is one of the middle schools located at Jalan Lieutenant Colonel. Hendro Suratmin Sukarame District, Bandar Lampung City. Based on the application of this school curriculum using a double track curriculum that aims to answer the needs of students. The implementation of community service activities uses presentation and practice methods. The presentation method is a way to communicate before many people to convey ideas, definitions, objectives and benefits related to things to be conveyed. As many as 53% of participants of this activity said they were satisfied with the implementation of the activityKeywords—Graphic Design, Generation Z, Competitive